ANALISIS PRODUKTIVITAS PEKERJAAN PONDASI BORED PILE (STUDI KASUS PADA BANGUNAN PERKANTORAN 31 LANTAI) - Abraham Putra Lesmana; Ratna S. Alifen (Jurnal Dimensi Pratama Teknik Sipil, 2015)
Deep foundation is commonly used on high rise buildings. In most big cities people often uses bored pile as their deep foundation because bored pile is undisplacement pile, which means it doesn’t replace the underground earth that will cause pressure to the surrounding buildings. Bored pile doesn’t cause sound pollution and has minimum vibration so it doesn’t harm the environment. This research’s goal is to analyze the productivity of bored pile construction and the factors which influencing it. This research uses unit completed method and multiple regression analysis to analyze the factors. The results of the mean productivity measurement of bored pile with diameter 800mm is 3,84 m’/hour/equipment. Decrement of productivity is influenced by factors of equipment (83,37 workhours lost;40,39%), environtment(5,52 workhours lost;2,68%), labor (63,3 workhours lost;30,66%), material (4,77 workhours lost;2,31%), and management (49,46 workhours lost;23,96%).